SYNTHESIS AND CHARACTERIZATION OF CATION DEFICIENT DIELECTRIC RESONATOR PEROVSKITE ELECTROCERAMICS - Tyagi, Anand K; Kaur, Karamveer (International Journal of Research -GRANTHAALAYAH, 2021)
Electroceramics are the ceramic materials that have been specially designed for specific electrical, electronic, optical or magnetic properties. The futuristic demands of Communication Technology require the advanced electroceramics that may efficiently perform the functions of various circuit elements. The performance of electroceramics and their devices is primarily dependent on the three factors namely; complex interplay between processing & chemistry, structure at many levels and device physics. This paper describes the Nano Science assisted synthesis of application grade complex titanate based electroceramics that are presently being used or have futuristic potential to be used in communication technology. A preparative scheme using Nano-powders generated by Auto-ignition method has also been outlined and phase development investigated. The optimized prepartional conditions have also been studied and complex titanates to be used as Dielectric Resonators (DR) are specially tailored to meet the demand and requirement of microwave applications for high performance and low-cost devices. The dielectric constants measured by sandwich method were found to be around 39 at 5 MHz frequency and all the samples were found to have Q-factor larger than 3500 that make the synthesized materials suitable to be used as DR in Microwave Communication Technology.